Philippine Studies in China Background, Achievements, and Opportunities Through the Perspective of Country and Region Studies - Ma, Yuchen (2025)
Since 1949 Philippine studies in China has evolved from being limited to historical research to having a multidisciplinary approach. In the early twenty-first century, diversification and knowledge base construction began, with a “policy turn” in the 2010s redirecting its focus toward contemporary political, economic, and social issues aligned with China’s strategic interests. This shift deepened bilateral understanding and enriched the field theoretically and materially. In 2022 the establishment of country and region studies (CRS) emphasized an autonomous knowledge system about foreign countries, prompting institutional and individual adaptations. These developments have fostered research diversification, theorization, and comprehensive knowledge construction, creating opportunities for scholarly cooperation and productive China–Philippines relations.
Keywords: China--Relations--Philippines; Philippines--Relations--China; Philippine studies; Cross-cultural studies